2022
DOI: 10.15835/nbha50212732
|View full text |Cite
|
Sign up to set email alerts
|

Pot Aloe vera gel – a natural source of antioxidants

Abstract: Aloe vera (Aloe barbadensis Miller) is widely spread around the world and it is used in the food and cosmetic industry and traditional medicine due to its high content in bioactive compounds. Thus, this article investigated the phenolic compounds of Romanian Aloe vera gel and its antioxidant capacity.  The gel was extracted using 4 different solvents: methanol, ethanol, water, and acetone. Total phenolics were measured by the Folin-Ciocalteu method, total flavonoids by aluminium chloride reaction, and the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Literature reports that some flavonoids in plants do exhibit potential antiviral activities (Wang et al 2020). Aida et al (2022) found the methanolic extract of Aloe vera to exhibit the highest polyphenol content, while ethanolic extract showed the highest flavonoid content. Flavonoids were found to be present in A. ferox across the samples, which supports the use of A. ferox as a medicinal plant.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports that some flavonoids in plants do exhibit potential antiviral activities (Wang et al 2020). Aida et al (2022) found the methanolic extract of Aloe vera to exhibit the highest polyphenol content, while ethanolic extract showed the highest flavonoid content. Flavonoids were found to be present in A. ferox across the samples, which supports the use of A. ferox as a medicinal plant.…”
Section: Resultsmentioning
confidence: 99%
“…Total polyphenols content (TPC) was evaluated using Folin–Ciocalteu as previously described by Pop et al [ 30 ]. Ginger root capsules extract (25 μL of) was mixed with Folin–Ciocalteu reagent (125 μL; 0.2 N) and sodium carbonate (Na 2 CO 3 ) solution (100 μL; 7.5% w / v ), homogenized, put in 96-well plates and incubated at room temperature in dark conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The High-Performance Liquid Chromatography–Mass Spectrometry (HPLC-MS) analysis of GRCE was performed as described by Pop et al [ 30 ]. Agilent 1200 HPLC with DAD detection was coupled to Agilent 6110 single quadrupole mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of studies have reported diverse classes of phytochemicals (Table 2) in Aloe species using different methods [17,[25][26][27][51][52][53][54][55][56][57][58]. Sathyaprabha et al [51] found tannins, saponins, terpenoids, flavonoids, steroids, cardiac glycosides, phlobatannins, squalene oleic acid and dodecanoic acid in A. vera.…”
Section: Phytochemistry Of a Veramentioning
confidence: 99%
“…Antioxidants are a group of compounds that inhibits the free radicals and lipid oxidation reactions in the body [36,77,78]. A lot of studies have described the antioxidant activity of the A. vera plant [27,57,58,70,[79][80][81][82] and the details of antioxidant activity conducted globally using various methods are given in Table 3.…”
Section: Antioxidant Activitymentioning
confidence: 99%